Proceedings From the 3rd Symposium of the World Database for Pediatric and Congenital Heart Surgery (2019)
The World Database for Pediatric and Congenital Heart Surgery was created to provide a resource for centers to be able to perform complex outcomes analyses of children undergoing repair of a congenital heart defect. In just under two years, the World Society for Pediatric and Congenital Heart Surgery (WSPCHS) has amassed over 13,000 procedures from 55 centers into the database. This Proceedings of the 3rd World Database Symposium held at the 6th Scientific Meeting of the WSPCHS summarizes the presentations of international experts in the fields of outcomes analysis and care of children with congenital heart surgery.